Abundance and diversity of soil arthropods in the secondary forest and park at the University of Bengkulu - Ariffatchur Fauzi; Dwinardi Apriyanto; Agustin Zarkani; Sugeng Santoso; Maulana I Kamil; Hariz E Wibowo (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Soil ecosystems are ecosystems related to the degradation of organic matter. University of Bengkulu is an area that has two kinds of soil ecosystems; secondary forest ecosystems and park ecosystems. Arthropods are one of the faunas living in the University of Bengkulu campus ecosystem. Camponotus dominates the secondary forest area, while Solenopsis dominates the park ecosystem. Data were obtained from two ecosystems (secondary forest ecosystem and park ecosystem). The results show that there are five classes with 199 individuals, while in the park ecosystem, there are four classes with 250 individuals.The secondary forest ecosystem diversity index value is 2,73, and the ecosystem diversity index value is 1,91. The evenness index value of the secondary forest ecosystem is 0,78, and the park ecosystem is 0,76. The secondary forest ecosystem dominance index value is 0,09, and the park ecosystem dominance index is 0,17. The diversity of soil arthropods in secondary forest and park ecosystems is in the category of moderate diversity. The even distribution of soil arthropods in both ecosystems is high. Moreover, there is no dominance by one type of soil arthropods in both ecosystems. The diversity of arthropods in the secondary forest ecosystem is higher than that of the park ecosystem. The number of individuals in the park ecosystem is higher than in the secondary forest ecosystem. In both ecosystems, the most commonly found are from the Formicidae family